The dynamic analysis of stress state of the piston rod of single-stage long-stroke piston compressor - D. I. Chernyavsky; D. D. Chernyavsky (Омский научный вестник)
The analysis of loaded state of system piston rod – piston of single-stage longstroke piston compressor is performed. These compressors are used to change the compressed gas pressure from normal atmospheric pressure (760 mmHg = =0,101 MPa) to discharge pressure (2–10 MPa). The criteria for calculating the piston rod from the point of view of its dynamics, taking into account the natural vibration frequency of the piston rod, are determined. Conclusions are drawn and practical recommendations are given that can be used in the design process of these compressor stages.